SINERGISITAS BADAN NARKOTIKA NASIONAL DENGAN KANTOR BEA CUKAI KOTA DUMAI DALAM MENCEGAH PENYELUNDUPAN NARKOBA TAHUN 2021 - Arief Budiman; Zulfa Harirah (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The synergy of the customs agency with the national narcotics agency in preventing narcotics smuggling is cooperation in a relationship and institutional or agency setting with a specific division of tasks to produce a good goal, through communication and coordination, therefore the author is interested in further studying the formulation of the problem.